Hacking and penetration testing with low power devices - Polstra, Philip (Syngress, 2015)
This book shows how to perform penetration tests using small, low-powered devices that are easily hidden and may be battery-powered. It shows how to use an army of low-cost devices from distances of a mile or more. Polstra shows how to use various configurations, including a device the size of a deck of cards that can easily be attached to the back of a computer. Devices running a version of The Deck, a full-featured penetration testing and forensics Linux distribution, that can run for days or weeks on batteries due to their low power consumption, are discussed. You will also learn how to configure and use open-source tools, and how to leverage IEEE 802.15.4 networking to perform penetration tests from up to a mile away, or use 802.15.4 gateways to perform pen tests from anywhere in the world. --
Print version record
Keywords: Penetration testing (Computer security) -- Equipment and supplies; BeagleBone (Computer); BeagleBone (Ordinateur)